ANALISIS ISODOSIS TEKNIK TIGA DIMENSI DENGAN LAPANGAN KRANIOSPINAL PADA PASIEN ANAK - Sari, Radila Mawar; Natalisanto, Adrianus Inu; Perwitasari Sutaji Putri, Devina Rayzy (Progressive Physics Journal, 2023)
Craniospinal is known as the method to kill the cancer within a wide radiation area, starting from the cranial to spinal nervous system. In the case, the cancer has spread through the fluid of cerebro spinalis, such as medulloblastoma. We carried out the research to determine the isodose curve in medulloblastoma craniospinal patients and DVH (Dose Volume Histogram) statistic in the OAR (Organ at Risk) by using 3D-CRT radiotherapy technique. To conduct the radiative treatment, we used the moving Junction method in which the radiation was divided into three Iso section, i.e.: Section Iso brain with gantry 90° and 270°, Section Iso thoracic with gantry 0°, and Section Iso lumbar with gantry 0°. Then, we analyzed the isodose curves and DVH statistics created by photon beams of 6 MV and 10 MV with and without considering the dose absorbed by OAR. We found that the isodose curves created with considering the OAR dose were better than those created without considering the OAR dose. We also found that the dose absorbed by OAR was within the tolerance limit stated in ICRU guidelines. Kata Kunci: DVH of statistic, Isodose curve, Craniospinal, Medulloblastoma